Why some EU institutions litigate more often than others: exploring opportunity structures and actor motivation in horizontal annulment actions. Issue 6 (19th September 2018) - Hartlapp, Miriam
ABSTRACT: EU scholars have studied mobilization as a cross-level phenomenon. Individuals and organized interests seek preliminary rulings with the Court of Justice of the EU to challenge national rules. Likewise, the Commission takes member states to court where they infringe commonly agreed rules. However, litigation can also run horizontally in the EU system. EU institutions can go to court to annul actions of other EU institutions. Studying this so far neglected phenomenon of litigation, the paper analyses differences in mobilization across European Parliament, Council and Commission. To this aim it conceptualizes litigation decisions as resulting from an interplay of agency and structure. Decision-making within organizations and in the EU political system as well as different motivations of actors are presented to explain differences in horizontal litigation. Methodologically the analysis combines a database covering 160 horizontal annulment conflicts (1957 to 2017) and case studies based on expert interviews.